Leaf anatomy as a contribution to the taxonomy of Salacioideae N.Hall, ex Thorne & Reveal (Celastraceae) - Alvarenga Gomes, Sandra Maria; Lombardi, Julio Antonio [UNESP] (Springer Wien, 2010)
The current classification systems recognize Salacioideae as a monophyletic group within Celastraceae. Nonetheless, some divergences exist for genera: in some cases, most species of the subfamily have been included in only two genera; in others, these genera have been subdivided. This study characterizes the leaf anatomy of 31 species of the subfamily Salacioideae as a contribution to identifying them through features that may also help distinguish among genera. Cross-sections of the median region of the leaf blade and of the petiole and dissociated and macerated epidermis were analyzed. Taxonomically relevant anatomical characters include the type of crystals in the parenchymatous tissue (monocrystals in Cheiloclinium and druses in other genera); the presence of laticifers in Cheiloclinium and Tontelea only; the variable form of the petiole vascular system among studied species; the type of stomata (cyclocytic with two concentric circles of subsidiary cells in P. dulcis; anomocytic in T. attenuata, T. fluminensis, and T. leptophylla; laterocytic in C. anomalum and C. hippocrateoides; and ciclocytic in the other species); the sinuosity of the anticlinal walls of the epidermal cells (sinuous in Cheiloclinium and Peritassa, except P. laevigata, and in S. arborea, S. insignis, S. mosenii, S. nemerosa, and S. opacifolia, and straight in all other studied species); the presence of crystalliferous idioblasts in the epidermis of P. dulcis, P. flaviflora, and P. mexiae; and the presence, form, and disposition of sclereids in the leaf blade, which is a highly variable character among the studied species.
Keywords: Celastraceae; Salacioideae; Leaf anatomy; Taxonomy